Pandangan Dunia Pengarang Dalam Novel Putri Karya Putu Wijaya - Nur Hamidah (Journal of Feminism and Gender Studies, 2021)
Abstract Putri is a novel by Putu Wijaya part two that focuses on issues of Indonesian tradition in a specially with a female sword. This study was apply with genetic structuralism, to see the world view author. The method used in this research is the dialectical method. Data and source obtained from the words and paragraphs in the novel through the documentation process and interview with author and narasumber from Bali. The result and discussion of research inlcude, (1) novel structure, namely characters and themes. Characters in a Putri novel shows a picture social life of Balinese, while the theme is a Balinese tradition. (2) social life is influenced by family, education, where to live, and daily activity affect of creation. (3) the world view by Putu Wijaya in a Putri novel related with a traditions which grows and develops with the modernization. Putu Wijaya with a Balinese women succeede in making changes with the society’s view of Balinese tradition and women in the process totradition is in contact with the modernization of the realm, the freedom, social politic, and economic should be aligned and equal towards. Keyword : Putri novels, novel structure, author’s social life, author world view